2006
DOI: 10.1051/0004-6361:20065529
|View full text |Cite
|
Sign up to set email alerts
|

Five years of SGR 1900+14 observations withBeppoSAX

Abstract: We present a systematic analysis of all the BeppoSAX data of the soft gamma-ray repeater SGR 1900+14: these observations allowed us to study the long term properties of the source quiescent emission. In the observation carried out before the 1998 giant flare the spectrum in the 0.8-10 keV energy range was harder and there was evidence for a 20-150 keV emission, possibly associated with SGR 1900+14. This possible hard tail, if compared with the recent INTEGRAL detection of SGR 1900+14, has a harder spectrum (po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…The XMM-Newton power law plus blackbody parameters are in agreement with previous observations of this source carried out with ASCA (Hurley et al 1999c), BeppoSAX (Woods et al 1999b;Esposito et al 2007) and Chandra ), but the flux measured in September 2005 is the lowest ever seen from SGR 1900+14. A ∼30% decrease of the persistent emission, compared to the "historical" level of ∼10 −11 erg cm −2 s −1 , had already been noticed in the last BeppoSAX observation (Esposito et al 2007), that was carried out in April 2002, six month earlier than the last bursts reported before the recent reactivation.…”
Section: Xmm-newton Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The XMM-Newton power law plus blackbody parameters are in agreement with previous observations of this source carried out with ASCA (Hurley et al 1999c), BeppoSAX (Woods et al 1999b;Esposito et al 2007) and Chandra ), but the flux measured in September 2005 is the lowest ever seen from SGR 1900+14. A ∼30% decrease of the persistent emission, compared to the "historical" level of ∼10 −11 erg cm −2 s −1 , had already been noticed in the last BeppoSAX observation (Esposito et al 2007), that was carried out in April 2002, six month earlier than the last bursts reported before the recent reactivation.…”
Section: Xmm-newton Resultssupporting
confidence: 90%
“…A ∼30% decrease of the persistent emission, compared to the "historical" level of ∼10 −11 erg cm −2 s −1 , had already been noticed in the last BeppoSAX observation (Esposito et al 2007), that was carried out in April 2002, six month earlier than the last bursts reported before the recent reactivation. The long term fading experienced by SGR 1900+14 in 2002SGR 1900+14 in -2005 might be related to the apparent decrease in the bursting activity in this period.…”
Section: Xmm-newton Resultsmentioning
confidence: 68%
“…The pulsed fraction was significantly smaller than before the flare and the spin-down rate decreased. The following observations (Esposito et al 2007a;Mereghetti et al 2007), during which bursts were again detected, indicate that the source is still active although the flux levelled to the 2003 value.…”
Section: Sgr 1806-20mentioning
confidence: 81%
“…This continued monitoring has been extremely rewarding since in December 2004 SGR 1806−20 emitted the most powerful giant flare ever observed from an SGR (Hurley et al 2005;Mereghetti et al 2005a;Palmer et al 2005). The XMM-Newton data, coupled with similar monitoring programs carried out with ESO telescopes in the infrared band (Israel et al 2005) and at hard X-ray energy with INTEGRAL (Götz et al 2006) and Suzaku (Esposito et al 2007a), are used to study the connection between the persistent emission and the source activity level, as manifested by the emission of bursts and flares.…”
Section: Sgr 1806-20mentioning
confidence: 99%
“…The hard X-ray emission detected with INTEGRAL was fitted by a power law with photon index Γ ∼ 3.1, significantly steeper than that of other SGRs and AXPs (Götz et al 2006). Esposito et al (2007) reported the detection of hard (20−150 keV) X-ray emission from a region around SGR 1900+14 with the non-imaging spectrometer Phoswich Detection System (PDS, Frontera et al 1997) on board the BeppoSAX satellite. They modelled the observed X-ray emission with a power law with slope Γ ≈ 1.6.…”
Section: Introductionmentioning
confidence: 98%